Bilateral asymmetries and the performance profile in isokinetic knee assessment in young soccer players according to peak height velocity - Nicolau Melo de Souza; Luiz Fernando Ramos-Silva; Paulo Henrique Borges; Felipe Arruda Moura; Enio Ricardo Vaz Ronque; Julio Cesar da Costa (Revista Brasileira de Ciências do Esporte)
ABSTRACT The aim of the study was to compare isokinetic performance (PT) of knee extensors (ext) and flexors (flex), H:Q ratio, and PT asymmetry in young soccer players based on somatic maturation. 80 soccer players (aged 12-17) were sampled, classified as pre-PHV (n=19) and post-PHV (n=61). Isokinetic dynamometry assessed knee extensors/flexors at 60º/s. Pre-PHV had lower body mass/height than post-PHV (P < 0.001). Pre-PHV exhibited lower PT for dominant and non-dominant leg in ext and flex (P < 0.001). No differences in asymmetry (ext: 31.6% vs 31.1%; flex: 31.6% vs 34.4%) and H:Q ratio (dominant: 42.1% vs 32.8%; non-dominant: 26.3% vs 39.3%) between PHV groups, where asymmetry was considered >15%, and cutoff points for each limb H:Q were set at ≥60%. Study showed increased isokinetic performance according to PHV, but no effect on asymmetries and H:Q ratio.